Small Enterprises Environmental Management Practices in Terengganu, Malaysia - Yaacob, Mohd Rafi (Gyan Management Journal, 2010)
The presentstudy examines some small entrepreneurs' perceptions and environmental management practices in the state of Terengganu. Methodologically, this research used a mail survey method to gather information from varioustypesofsmallbusinesses,rangedfromfurniture,c/othesindustrytofoodprocessingbusinesses.Resu/tsofthis study provide insights into environmental management practices amongst small businesses in Terengganu in particularandMalaysiaingeneral.
Keywords: SmallEnterprises; EnvironmentalManagementPractices